Motivational Strategies to Develop L2 Student Engagement on Online Platforms - Lalitha B. Devi; Madhumathi P. (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
Online learning often becomes debatable with the question of how it could create motivation among disadvantaged learners or learners with low language proficiency levels. A classroom with mixed abilities is the biggest challenge for teachers to handle. But finding a one-size-fits-all solution will not be a viable option. Instead, providing a free space for students, using motivational stories in mother tongue, giving immediate feedback, posing reflective questions on different online platforms to engage students can act as a good motivational strategy to create a positive outlook among students regarding second language learning. The present research considers a sample of 114 students from various degree colleges in Telangana, India- who participated in a survey related to their perspectives on online Interaction, a story-based discussion conducted on WhatsApp, and a reflective discussion conducted on easyclass discussion board, an online tool. Students feel motivated when they were connected to the theme of the discussion or connected to the reflective questions posed in the discussion. Immediate feedback also motivates them instantly. It is observed that story-based discussion motivated students’ participation compared to the discussion on easyclass discussion board where questions related to personal experiences were asked. This implies teachers’ consideration of learner’s preferences of technological platform, motivational strategies, personal choices, time provided for students to interact and types of questions posed.